AU-DELÀ DES ROUTES, L'UTILISATION DES RESSOURCES LOCALES - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
En région rurale, les déplacements s'effectuent principalement